Pembangunan Website E-Commerce dengan Menggunakan Framework Laravel pada Eighter Production - Asep Nana Hermana; Abdurahman Jundi Rabbani; Irgilian Satria Pratama; Muhammad Ihsan; Mochamad Rafi Adi Saputra; Arda Nugraha; Andrie Anugrah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Eighter Production is a home industry that acts as a clothing manufacturer that offers various kinds of clothing products. Eighter Production provides various categories of clothing with various materials and colors. In an effort to further expand its reach in reaching consumers, Eighter Production utilizes internet technology as a medium for information, promotions and transactions.